THE EFFECTS OF CONTACT METAMORPHISMS IN ROCKS OF OLD “FRAME”OF THE KOROSTEN PLUTON - Mitrokhin, O.; Bilan, O.; Gruschynska, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The character of distribution, the mode of occurrence and the petrographic features of the contact-metamorphic rocks in the framework of Korosten anortosite-rapakivigranite complex of the Ukrainian Shield are studied. It is established that the exocontact of Korosten сomplex basic intrusions are formed by high-temperature contact-thermal rocks of pyroxene- hornfels facies which wrongly were accepted by predecessors for pyroxene gneisses of ancient granulite base. Contact influence of the main phase granite intrusions of Korosten complex on surrounding gneisses was showed, mainly, in formation of contact-thermal rocks of amphibol-hornfels and pyroxen-hornfels facies.